Impaired balance and neurodevelopmental disabilities among children with congenital cytomegalovirus infection. (15th August 2014) - Karltorp, Eva; Löfkvist, Ulrika; Lewensohn‐Fuchs, Ilona; Lindström, Katarina; Eriksson Westblad, Mimmi; Teär Fahnehjelm, Kristina; Verrecchia, Luca; Engman, Mona‐Lisa
Abstract Aim Although cytomegalovirus (CMV) is the most common congenital infection, existing research has not provided us with a full picture of how this can affect children in the future. The aim of this case–control study was to evaluate disabilities in a well‐defined group of children with congenital cytomegalovirus (CMV) infection, who had been fitted with cochlear implants because of severe hearing impairment. Methods A multidisciplinary team assessed 26 children with congenital CMV infection for balance difficulties, neurodevelopmental disabilities and language and visual impairment. We also included a control group of 13 children with severe hearing impairment due to connexin 26 mutations. Results The majority of the children with congenital CMV infection (88%) displayed balance disturbances, including walking at a later age, but there were no cases in the control group. The CMV group also displayed frequent neurodevelopmental disabilities and feeding difficulties. Conclusion Congenital CMV infection affects the general development of the brain and gives rise to a complex pattern of difficulties. Identifying comorbid conditions is very important, as children with associated difficulties and disabilities need more support than children with just hearing impairment. Congenital CMV infection needs to be considered in children with hearing impairment and/or balance disturbance and/or neurodevelopmental disabilities.